Shelter, five stories, five photographers - Habitat Project, - (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2017)
Gruppo Habitat Project Gianni Cipriano Jean Revillard Michela Frontino Henk Wildschut Roger Eberhard Habitat Project is a research platform for unconventional housing phenomena and their possible declinations. A collection of heterogeneous perspectives by photographers, artists and researchers in urban issues, dealing with potential forms of the contemporary living.